Green Faith? The Role of Faith-Based Actors in Global Sustainable Development Discourse. (1st June 2018) - Glaab, Katharina; Fuchs, Doris
Abstract : Ethical questions concerning global sustainability governance have been widely discussed with respect to the role of civil society in general. Interestingly, faith-based actors (FBAs) have so far attracted scant attention in this context. Yet FBAs actively participate in international political negotiations and public debates on sustainable development. Secularisation theory differentiates between religious and secular actors. To date, however, it remains unclear whether FBAs contribute a distinct faith-based perspective to global sustainable development discourse and, if so, what this perspective is. The present article aims to identify the relevant norms and ideas in FBAs' communications and to contrast them with other existing ideas on sustainable development. On the basis of a content analysis of the submissions by FBAs and non-faith based civil society groups in the context of the UN Rio+20 summit, the article first investigates what visions are contained in current articulations of FBAs with respect to sustainable development. Secondly, it explores in what way FBAs' ideas about sustainable development differ from those of secular civil society. Our analysis establishes a basis for further inquiries into the role of FBAs in global sustainable development discourse.